Issues and perspectives of building a regional system of donor services (on the example of Nizhny Novgorod region) - S. V. Romanov; O. P. Abaeva; O. Yu. Alexandrova; G. Yu. Smirnova (Вестник трансплантологии и искусственных органов, 2019)
Aim: to determine the perspectives of development a regional system of donor services (on the example of Nizhny Novgorod region) based on analysis of current results of its activity.Materials and methods. Protocols of the donor’s initial examination, acts of organ removal for transplantation, questionnaires of 266 doctors of donor bases in the region. Research methods: sociological, statistical.Results. The efficacy of the system of collaboration between the participants of organ donation existing in Nizhny Novgorod region is mainly determined by the activity of doctors on donor bases. According to the results of the questioning of doctors, the most significant factor determining their inclination to collaborate with the Center of organ donation is the direction by the administration of the medical organization (59,3 ± 3,0%). Only 11,1 ± 1,3% of the interviewed doctors stressed their understanding of the importance of the development of organ transplantation programs. As a result, the number of hospitals actually reporting the presence of donors was a half of the number established by the local administration of medical services in 2009. This indicator decreased more than 50% by 2017. During the period of 2009–2017, 488 calls of donor services were registered, while 354 calls ended up being ineffective mainly due to low level of qualification among the specialists of donor bases. During the examined period, there were registered 83 posthumous removals of donor organs with the death of the subjects being mainly (87,6 ± 3,4%) caused by an infarction of cerebral blood circulation. The losses of the donor resource resulted from inability to receive organs from persons who died as a result of injuries due to the rejection of their relatives (49 cases).Conclusion. Optimization of the use of the donor resource of the region is possible only if the development of the organ donation program is promoted at the level of the territorial public health authority. In the case of solving this issue, it is hypothetically possible for the region to achieve an indicator of donor activity of 25 per 1 mln. person.